Faktor Dominan Pada Deformasi Gelombang Bikromatik Multiarah - Toto Nusantara (Limits: Journal of Mathematics and Its Applications, 2006)
In this paper we consider to dominant factor of multidirectional bichromatic waves deformation. Third order solution of iKP equation with bichromatic signal at the boundary is used as a model of bichromatic waves. Due to dispersive and non linearity properties of wave model, bichromatic wave was deformed when propagated. By analysing of wave component, it was found that wave deformation due to ¯rst order and third order component side band and free waves.